SystematicLiteratureReview:PeranMetakognisidalam Meningkatkan Pemecahan Masalah Matematika - Rusdianto; Rezki Fadillah; Isyati Radiah; Nani Kurniati (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
Math problem-solving skills are essential skills that students must have to face academic and daily life challenges. One of the cognitive factors that plays an important role in improving this ability is metacognition, which is an individual's awareness and control of his or her own thought process. This study aims to analyze the role of metacognition in improving mathematical problem solving. The method used is Systematic Literature Review (SLR) by reviewing various empirical studies in the last five years. The results of the study showed that students with high levels of metacognition tended to be more effective in understanding, planning, and evaluating mathematical problem-solving strategies. In addition, the application of metacognitive strategies in learning can increase students' learning independence and critical thinking skills. The implications of this study confirm the importance of integrating metacognitive strategies in mathematics learning to improve students' problem-solving abilities optimally.